Environmental and Social Management System Implementation Handbook : Textiles and Apparel - International Finance Corporation (Washington, DC, 2014)
Today, textiles and apparel companies are confronted with a number of significant environmental and social challenges. None of the challenges are insurmountable, but if not effectively addressed and managed, they can hurt core business operations and profitability. Among these challenges are increasing energy and raw materials costs, the growing power and influence of environmental and labor regulatory agencies, and rapidly evolving consumer awareness and concerns about environmental and social issues. These risks are in addition to the primary risk of failing to build brand and consumer confidence. This Handbook is intended to be a practical guide to help companies in the textiles and apparel industry develop and implement an environmental and social management system, which should help to improve overall operations. If a company has existing management systems for quality or health and safety, this Handbook will help to expand them to include environmental and social performance. Sections I and II of this handbook provide background on environmental and social management systems (ESMS) in the textiles and apparel industry. Section III provides step-by-step instructions on how to develop and implement an ESMS. The ESMS Toolkit and Case Studies section gives tools for implement the systems described, as well as two case studies of companies in the food and beverage industry that implemented an ESMS. Finally, the ESMS Self-Assessment and Improvement Guide is a companion publication contains a questionnaire, maturity matrix, and improvement tips to help companies measure the maturity of their ESMS. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.